THE IMPACT OF THE TYPE OF CARE ON LONGEVITY IN UKRAINE - Nataliya I. Kitsera; Ruslan V. Kozovyi; Zoriana P. Dvulit; Larysa Ye. Kovalchuk; Maya V. Bondarenko (Клінічна та профілактична медицина)
Introduction. Parents play an important role in raising children. They develop their language, thinking, form their interests, aspirations, recognize the ability to talent. A father serves as an example of courage for children and teaches them to care for and protect others. A mother, in turn, forms the emotional foundation of the family, supports her children’s dreams and aspirations, and creates a sense of comfort at home. The family is a source of material and moral support for children, a means of preserving and transmitting cultural values and traditions from generation to generation.